Prarancangan Pabrik Furfural Dari Tandan Kosong Sawit Kapasitas 6000 Ton/Tahun Dengan Disain Alat Utama Reaktor Fluidized Bed - Ahmad Pratama; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Furfural needs in the country is increasing along with the development of industries such as paint industry, oil, pharmaceuticals, plastics and also polymer industry. Indonesia's furfural needs to date still rely on imports from other countries. Fufural is commonly produced using agricultural waste containing pentosan, such as rice husks, corn cobs, wood, hemp, cane pulp, empty fruit bunches and other sources containing fiber. Indonesia is a resource-rich country that has the potential to produce raw materials for fufural production, one of which is empty fruit bunches with a pentosan content of 25.90%. The amount of waste of empty fruit bunches throughout Indonesia in 2004 has reached 18.2 million tons. The process of making furfural with Supra yield process takes place in a solid-gas phase batch reactor, at a temperature of 206°C and a pressure of 18 atm where the hemicellulose in biomass is converted through 2 reaction stages, hydrolysis and dehydration. The conversion process with a reaction time of 15-20 minutes and using sulfuric acid catalysts as much as 3% of the feed mass. The design result was obtained reactor with a height of 26.05 m and diameter of 6.25 m and equipped with internal cyclone as separator between solid particles attached to the gas product. The evaluation of the factory design economic analysis shows that the factory is eligible to be established with the factory's Return On Invesment (ROI) of 26.65%, the Break Event Point (BEP) is 35%, the Internal Rate of Return (IRR) is 22.74%, and the factory Payback Period (PBP) is 2.75 years.  Keywords: Batch Reactor, Furfural, Pentosan, Suprayield